Peran Budaya Organisasi dan Disiplin Kerja dengan Mediasi Motivasi Kerja terhadap Kinerja Pegawai di Badan Kesatuan Bangsa dan Politik Kota Denpasar - Ni Kadek Lisnayanti; Ni Made Yudhaningsih; Ni Luh Indiani (PT. PENERBIT TIGA MUTIARA, 2025)
This study is motivated by the importance of understanding the factors that influence employee performance within governmental organizations, particularly in the National Unity and Political Agency (Bakesbangpol) of Denpasar City. The primary objective of this research is to analyze the effects of organizational culture and work discipline on employee performance, while also examining the mediating role of work motivation. Employing a quantitative approach and path analysis method, the study involved all employees of Bakesbangpol Denpasar using a saturated sampling technique. The findings reveal that organizational culture does not have a significant direct effect on employee performance, whereas work discipline exerts a positive and significant influence. Work motivation emerges as a crucial factor affecting performance, with a path coefficient of β = 0.440 and a significance value of 0.000. Although organizational culture significantly influences work motivation, it does not directly impact performance. In contrast, work discipline does not significantly affect motivation. Notably, work motivation significantly mediates the relationship between organizational culture and employee performance, but not the relationship between work discipline and performance. These findings underscore the pivotal role of work motivation as a mediating variable that enhances the impact of organizational culture on performance improvement. With an R value of 0.695 and an Adjusted R² of 0.683, the model explains 68.3% of the variance in employee performance, with the remaining 31.7% attributed to other factors outside the model. The novelty of this study lies in mapping the structural relationships among organizational culture, work discipline, and motivation as a mediating variable within the context of a local governmental institution an area that has been empirically understudied.